Intracranial epidural bleeding : history, management, and pathophysiology - Ganz, Jeremy C., 1943- (Academic Press, an imprint of Elsevier, 2017)
Intracranial Epidural Bleeding: History, Management, and Pathophysiology examines the history of the concepts underlying the understanding of the clinical features of epidural bleeding. The pathophysiology of epidural bleeding was examined in two PhD theses in the 1980s, with the results published in top international journals. However, these concepts have not been understood by the general neurosurgical community. This book provides a comprehensive overview of how epidural bleeding actually works. It can be used to help improve the interpretation of images during management, and to assess degrees of urgency. This book is written for neurosurgeons, neurologists, cerebrovascular physiologists, trauma surgeons, and medical historians.